The translation of humanity into prison design: How do the new, standardised “Model 2015” prison buildings meet normative demands in Norwegian crime policy? Przełożenie zasad humanitaryzmu na projektowanie więzień. Jak nowe, wystandaryzowane zgodnie z „Modelem 2015”, budynki więzienne spełniają normatywne wymogi norweskiej polityki kryminalnej? (Archives of Criminology, 2023)
Prison architecture reflects the ideas and values of a penal policy, providing insights into punishment philosophies. In Norway, normalisation, resettlement and dynamic security norms have shaped correctional care. Based on a mixed method study, this article examines how these norms are translated into “Model 2015” prisons. Despite spaces for positive prisoner relationships, the design faces challenges in escaping pervasive systems of control and discipline. Architectural boundaries obstruct dynamic security and impede the staff’s involvement in resettlement. Inadequate facilities for prisoner progression and daytime activities further undermines these processes. While some architectural and technological initiatives aimed at normalising prison life have proved successful, they tend to normalise not only the prison environment, but also the prisoners. The study demonstrates architecture’s critical role in realising humane prison conditions and emphasises the need for humane design.